2013
DOI: 10.1128/aem.00380-13
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Functions of Phosphotransferase System Genes in the Genome of the Lactic Acid Bacterium Oenococcus oeni

Abstract: Oenococcus oeni, the lactic acid bacterium primarily responsible for malolactic fermentation in wine, is able to grow on a large variety of carbohydrates, but the pathways by which substrates are transported and phosphorylated in this species have been poorly studied. We show that the genes encoding the general phosphotransferase proteins, enzyme I (EI) and histidine protein (HPr), as well as 21 permease genes (3 isolated ones and 18 clustered into 6 distinct loci), are highly conserved among the strains studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…The genes mfs0819 and mfs1574 were shown to be highly overexpressed during cultures of O. oeni B1 (no genome available) on glucose, and the glucose uptake activity of the encoded proteins was demonstrated by heterologous expression in Bacillus subtilis [21]. The gene mfs0136 was slightly overexpressed in the presence of glucose, but the activity of the encoded protein has not been demonstrated [22]. The manB operon was shown to be overexpressed during cultures on glucose and fructose [21, 22].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The genes mfs0819 and mfs1574 were shown to be highly overexpressed during cultures of O. oeni B1 (no genome available) on glucose, and the glucose uptake activity of the encoded proteins was demonstrated by heterologous expression in Bacillus subtilis [21]. The gene mfs0136 was slightly overexpressed in the presence of glucose, but the activity of the encoded protein has not been demonstrated [22]. The manB operon was shown to be overexpressed during cultures on glucose and fructose [21, 22].…”
Section: Resultsmentioning
confidence: 99%
“…The gene mfs0136 was slightly overexpressed in the presence of glucose, but the activity of the encoded protein has not been demonstrated [22]. The manB operon was shown to be overexpressed during cultures on glucose and fructose [21, 22]. In Champagne strains, which exhibit a particularly slow growth compared to the others (μ ≈ 0.35 day −1 against 0.6–0.7 day −1 for most strains), several genes associated with glucose catabolism seem singular: the gene mfs1574 is truncated while Mfs0136 and ManB display specific protein sequences.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our preliminary analysis indicated that the number of PTS-related proteins, particularly the PTS enzyme II genes for fructose and mannose family, significantly varied in three completed L. casei genomes . In contrast, genes encoding PTS systems are highly conserved in O. oeni strains (Jamal et al 2013). L. casei is a versatile microorganism that can be found in various niches, whereas O. oeni is indigenous to wine or similar niches.…”
Section: Metabolic and Biosynthetic Capabilitiesmentioning
confidence: 99%